Reduced uptake of [11C]‐ABP688, a PET tracer for metabolic glutamate receptor 5 in hippocampus and amygdala in Alzheimer's dementia. Issue 6 (18th April 2020) - Treyer, Valerie; Gietl, Anton F.; Suliman, Husam; Gruber, Esmeralda; Meyer, Rafael; Buchmann, Andreas; Johayem, Anass; Unschuld, Paul G.; Nitsch, Roger M.; Buck, Alfred; Ametamey, Simon M.; Hock, Christoph
Abstract: Introduction: Metabotropic glutamate receptors play a critical role in the pathogenesis of Alzheimer's disease due to their involvement in processes of memory formation, neuroplasticity, and synaptotoxity. The objective of the current study was to study mGluR5 availability measured by [ 11 C]‐ABP688 (ABP) in patients with clinically diagnosed Alzheimer's dementia (AD). Methods: A bolus‐infusion protocol of [ 11 C]‐ABP688 was applied in 9 subjects with AD and 10 cognitively healthy controls (Controls) to derive distribution volume estimates of mGluR5. Furthermore, we also estimated cerebral perfusion by averaging early frame signal of initial ABP bolus injection. Results: Subjects with Alzheimer's dementia (mean age: 77.3/ SD 5.7) were older than controls (mean age: 68.5/ SD : 9.6) and scored lower on the MMSE (22.1/SD2.7 vs. 29.0/SD0.8). There were no overall differences in ABP signal. However, distribution volume ratio (DVR) for ABP was reduced in the bilateral hippocampus (AD: 1.34/ SD : 0.40 vs. Control: 1.84/ SD :0.31, p = .007) and the bilateral amygdala (AD:1.86/ SD :0.26 vs. Control:2.33/ SD :0.37 p = .006) in AD patients compared to controls. Estimate of cerebral blood flow was reduced in the bilateral hippocampus in AD (AD:0.75/ SD :0.10 vs. Control:0.86/ SD :0.09 p = .02). Conclusion: Our findings demonstrate reduced mGluR5 binding in the hippocampus and amygdala in Alzheimer's dementia. Whether this is due to synaptic loss and/or consecutive reduction of potential binding sites or reflects disease inherent mechanisms remains to be elucidated in future studies. Abstract : The objective of the current study was to study mGluR5 availability measured by [11C]‐ABP688 in patients with clinically diagnosed Alzheimer's dementia. Our findings demonstrate reduced mGluR5 binding in the hippocampus and amygdala in Alzheimer's dementia.